80 Plantaris Injuries In Elite Uk Track And Field Athletes From 2009 To 2013. (5th September 2014) - Pollock, Noel; Calder, James; Dijkstra, Paul; Chakraverty, Robin
Abstract : Introduction: Recent cadaveric studies have identified a plantaris tendon in 98–100% of specimens (Saxena, 2000; van Sterkenberg 2007) and a number of studies have identified a potential relationship between the plantaris tendon and the development of Achilles tendinopathy (van Sterkenberg 2007; Alfredson 2011; Lintz 2011). There are a number of small published case series on the surgical removal of the plantaris tendon (Pearce, 2012; Alfredson, 2011) but no studies on the incidence, nature and management of plantaris injuries in a sporting population. This study reports plantaris injuries in an elite cohort of 214 British Track and Field athletes over a 4 year period, from 2009 – 2013. Methods: 214 athletes supported by the British Athletics Medical team between 2009 and 2013 were included in the study. An injury was recorded if a plantaris injury was diagnosed, recorded in the Electronic Medical Record and confirmed with imaging or surgical findings. Patient demographics and injury outcomes were recorded. Results: There were 33 new plantaris injuries in this cohort, representing an annual incidence of 6.4% of all athletes and 8.6% of all sprinters. All diagnoses were confirmed with imaging or surgical findings and included plantaris rupture, plantaris partial tear or plantaris tendinopathy/plantaris friction syndrome. There were 4 complete plantaris ruptures (Figure 1 ), 4 partial tears and 25 cases of plantaris tendinopathy/plantaris friction syndrome (Figure 2 ). There was a significant difference in injured limb site with more right side only plantaris injuries in bend running sprinters (Figure 3 ) Of the athletes who had a plantaris presentation, 74% also had Achilles tendinopathy at some point during the study period. Seventeen plantaris tendons were surgically removed from 13 athletes. 9/13 had good or excellent outcomes with return to elite level competition without symptoms. Discussion: The plantaris tendon is stiffer and stronger than the Achilles tendon demonstrating less capacity for elongation in response to load (Lintz, 2011). These different mechanical properties could result in a friction induced inflammatory reaction between the Achilles and plantaris. Continued peri-tendon inflammation may induce tendinopathic changes directly through neuro-inflammatory mediation (Andersson, 2007) or via a compressive mechanism. There appears to be a relationship with Achilles tendinopathy that requires further prospective investigation. There may be biomechanical reasons that predispose the plantaris to injury in elite track and field athletes. It has a long thin tendon which should confer elastic energy return and be of importance in sprinting athletes, who require large plantar flexor forces, throughout the full range. The plantaris tendon has been often ignored in presentations of Achilles region pain. This study demonstrates that plantaris pathology is common and suggests that preventative and management strategies are necessary for clinicians working with athletes. References: Saxena et al . Foot Ankle Int 2000 21(7):570–2 Van Sterkenburg et al . J Anat. 2011 218(3):336–41 Alfredson et al . BrJ Sports Med 2011 45(13)1023–5 Lintz F, et al . Foot Ankle Surg. 2011 17(4):252–5 Pearce CJ, et al . Foot Ankle Surg. 2012 18(2):124–7 Alfredson, et al . BrJ Sports Med . 2011 45(5):407–10 Andersson, et al . KSSTA 2007;15(10):1272–9